Pharmacophore Optimization Of Berberine As HER2 Inhibitor - Mohammad Rizki Fadhil Pratama; Guntur Satrio Pratomo (Fakultas Farmasi Universitas Setia Budi, 2017)
Previous research has shown that berberine, an alkaloid found in several plants such as akar kuning (Arcangelisia flava) shows the potential for inhibition of Human epidermal receptor-2 (HER2). Pharmacophore modification on the berberine was predicted could increase the affinity of berberine derivatives against HER2. The present study aims to determine the main pharmacophore of berberine with the highest influence towards berberine affinity against HER2. Molecular docking was performed on several modified pharmacophore of berberine against HER2. The docking results show that O atom at position number 23 has the most important influence on the berberine affinity towards HER2, where modification of O atom resulting in a decrease of berberine affinity. The highest affinity showed by derivate berberine-6 with the free energy of binding score and dissociation constant -10.80 kcal/mol and 12.17 nM, respectively. In contrast with other berberine derivatives, the berberine-6 derivate does not interact with the amino acid threonine at position 862. It provides a prediction that interaction of that amino acid potentially decrease the berberine activity towards active site of HER2. Further, derivate berberine-6 could be developed into HER2 inhibitor and should be potential to be developed as HER2-positive breast cancer therapy.